URGENSI MARGER BANK UMUM SYARI’AH MILIK NEGARA: TINJAUAN ANALISIS KOMPARATIF EFISIENSI DAN KINERJA KEUANGAN BANK SYARIAH BUMN - Setiawan, Dani; Rabbani, Abdullah Arkan; Munir, Muhammad Misbachul (Diponegoro Journal of Islamic Economics and Business, 2021)
Syariah financial industry has positive trend in the midst of increasingly fierce competition among banks. The growth of syariah banking making competition among banks in the field of its products and also services provided to costumer. Merger and acquisition option for syariah banks are one effort to enhance its economic of scale and also profitability. Three syariah banks which are merged, viz PT Bank BRI Syariah Tbk (BRIS), PT Bank Mandiri Syariah (BSM) and PT Bank BNI Syariah (BNIS). Goal of this research is by measure and compare efficiency and financial performance these banks. Data Envelopment Analysis (DEA) is used to measure efficiency whereas Maqasid Sharia Index (MSI) for financial performance. By using quarterly data from I-March 2015 to II-June 2020, result of DEA shows that operational income is a variable that gives much weight on the rise of syariah banking efficiency by 37,71%, followed by financing variable that gives 37,64%. Furthermore, MSI shows that BRIS is in the first rank, followed by BNIS and in the third rank is BSM. Based on profitability indicator, BNIS is in the top, followed by BSM in the second place and BRIS in the third place.